Cholinesterase inhibitors-associated torsade de pointes/QT prolongation: a real-world pharmacovigilance study - Zhang, Ni; Gan, Lanlan; Xiang, Guiyuan; Xu, Jing; Jiang, Tingting; Li, Yanping; Wu, Yuanlin; Ni, Rui; Liu, Yao (Frontiers in Pharmacology, 2024)
Objective: Cholinesterase inhibitor (ChEIs) is the first-line drug for Alzheimer's disease (AD). Understanding torsade de pointes (TdP)/QT prolongation with different ChEIs is essential for its safe and rational administration. This study aimed to evaluate the correlation between different ChEIs and TdP/QT prolongation. Methods：All ChEIs related TdP/QT prolongation cases were retrieved from the FAERS database using standard MedDRA query (SMQ) from the first quarter of 2004 to the third quarter of 2022. Disproportionality and sensitivity analysis were used to determine the signal of TdP/QT prolongation related to ChEIs. Results：557 cases of TdP/QT prolongation related to 3 ChEIs were searched by SMQ. The patients were mostly elderly people, with markedly more female than male. The signals of TdP/QT prolongation for ChEIs were detected by disproportionality analysis, and the signal of Donepezil was the strongest. The sensitivity analysis results indicate a robust and stable correlation between these signals with ChEIs. TdP/QT prolongation usually occurs within one month after taking ChEIs. The drug with the highest frequency of combination with donepezil and galantamine is citalopram, and the drug with the highest frequency of combination with rivastigmine is atorvastatin. Conclusion：The signals of TdP/QT prolongation related to ChEIs were strong and stable. It is necessary to be vigilant about the TdP/QT prolongation of various ChEIs, especially in elderly women, the initial stage after taking ChEIs, and when ChEIs combining with drugs that could prolong the QT interval.